2011
DOI: 10.1590/s0080-62342011000400025
|View full text |Cite
|
Sign up to set email alerts
|

Participação americana na formação de um modelo de enfermeira na sociedade brasileira na década de 1920

Abstract: The objectives of this historical-social study are: to describe the circumstances that determined the participation of North American nurses in the formation of the Brazilian nurse; and analyse the process of implementing institutional rituals as a strategy of symbolic fight, to confer visibility to the nurse profession and discuss the symbolic effects of institutional rituals for the consecration of a nurse model for Brazilian society at the time. The primary sources are constituted of pertaining written and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 8 publications
0
4
0
11
Order By: Relevance
“…This was the case for the Professional School of Nursing, which was created as an annex to the National Hospice for the Insane in the city of Rio de Janeiro by Decree 791 of 09/27/1890 (2)(3) . With the advancement of the public health movement, doctors from the National Department of Public Health realized that there was a need for qualified nursing professionals to work in tuberculosis services at the time, especially in the capital city of Rio de Janeiro (4) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was the case for the Professional School of Nursing, which was created as an annex to the National Hospice for the Insane in the city of Rio de Janeiro by Decree 791 of 09/27/1890 (2)(3) . With the advancement of the public health movement, doctors from the National Department of Public Health realized that there was a need for qualified nursing professionals to work in tuberculosis services at the time, especially in the capital city of Rio de Janeiro (4) .…”
Section: Introductionmentioning
confidence: 99%
“…She was from the International Health Board, linked with the Rockefeller Foundation. As part of that action, a survey on the nursing situation in the country was carried out in 1921; it revealed that the existing schools did not meet a minimum standard, and that it would be necessary to adapt the North American system to give a boost to Brazilian nursing (2)(3)5) . With 13 other American nurses, Parsons proposed the creation of a nursing service within the National Department of Public Health, which rose to prominence because it was the first nursing service in the world to be created at the federal level.…”
Section: Introductionmentioning
confidence: 99%
“…Para Marinho (2001) (Moreira, 1999;Santos, Faria, 2004;Amador, 2008). Entretanto, em 1920, no Brasil, (Moreira, 1999;Santos, Faria, 2004;Santos et al, 2011). (Moreira, 1999;Santos et al, 2011).…”
unclassified
“…A missão ficou conhecida como "Missão Parsons", porque foi liderada pela enfermeira americana Ethel Parsons, antiga diretora do Bureau of Child Hygiene and Public Nursing da Secretaria de Saúde do Texas, que chega ao Brasil, em 2 de setembro de 1921, para realizar um levantamento das condições do País e, assim, implantar um serviço de enfermagem mais qualificado e nos moldes dos padrões norte-americanos (Moreira, 1999;Santos, Faria, 2004;Carvalho, 2008;Santos et al, 2011).…”
unclassified
See 1 more Smart Citation